2015
DOI: 10.1021/ja511476n
|View full text |Cite
|
Sign up to set email alerts
|

Parahydrogen-Induced Polarization by Pairwise Replacement Catalysis on Pt and Ir Nanoparticles

Abstract: Pairwise and random addition processes are ordinarily indistinguishable in hydrogenation reactions. The distinction becomes important only when the fate of spin correlation matters, such as in parahydrogen-induced polarization (PHIP). Supported metal catalysts were not expected to yield PHIP signals given the rapid diffusion of H atoms on the catalyst surface and in view of the sequential stepwise nature of the H atom addition in the Horiuti-Polanyi mechanism. Thus, it seems surprising that supported metal hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
81
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 39 publications
11
81
1
1
Order By: Relevance
“…HET-PHIP effects were also successfully observed using heterogeneous catalysts comprising Pt and Pd nanoparticles supported on γ-Al 2 O 3 , [79] and later for many other supported metals (e.g., Rh, Ir, Co, Ni, Au, Cu) catalysts in gas, liquid and aqueous phase hydrogenations. [1112, 25, 27, 78f, 78g, 80] Variation of the type of metal, metal particle size [80a, 80d, 81] and shape, [80e, 80h] type of support [80a, 80d, 80g, 80i] and reaction conditions were all shown to influence the magnitude of the PHIP effect. Polarization transfer from 1 H to heteronuclei ( 13 C, 15 N) during heterogeneous hydrogenation [9b, 62a, 62b] helps to increase the hyperpolarization lifetime significantly, and is particularly important for potential biomedical applications along with the use of aqueous media.…”
Section: How To Make It Work: the Hyperpolarizer And Chemistry Of mentioning
confidence: 99%
“…HET-PHIP effects were also successfully observed using heterogeneous catalysts comprising Pt and Pd nanoparticles supported on γ-Al 2 O 3 , [79] and later for many other supported metals (e.g., Rh, Ir, Co, Ni, Au, Cu) catalysts in gas, liquid and aqueous phase hydrogenations. [1112, 25, 27, 78f, 78g, 80] Variation of the type of metal, metal particle size [80a, 80d, 81] and shape, [80e, 80h] type of support [80a, 80d, 80g, 80i] and reaction conditions were all shown to influence the magnitude of the PHIP effect. Polarization transfer from 1 H to heteronuclei ( 13 C, 15 N) during heterogeneous hydrogenation [9b, 62a, 62b] helps to increase the hyperpolarization lifetime significantly, and is particularly important for potential biomedical applications along with the use of aqueous media.…”
Section: How To Make It Work: the Hyperpolarizer And Chemistry Of mentioning
confidence: 99%
“…30,31 The main disadvantage of this approach is the presence of the dissolved homogeneous catalyst, which is expensive and is challenging to separate from the hyperpolarized compounds. 32,33 Recently, however, PHIP was observed in the heterogeneous reactions in the gas 34 and in the liquid phases 35,36 over immobilized complexes, 37 supported metals 34,38 and ligand-capped nanoparticles. 39,40 Observation of 13 C HP resonance and therefore, production of 13 C-hyperpolarized molecules via heterogeneous hydrogenation with parahydrogen was so far shown only for 13 C HEP during hydrogenation of 2-hydroxyethyl acrylate over platinum nanoparticles capped with glutathione.…”
mentioning
confidence: 99%
“…Therefore, understanding the nature of active sites that can add two hydrogen atoms from the same hydrogen molecule as ap air to asubstrate molecule is ah ighly important task. [9][10][11] Recently,i tw as shown that the nature of the catalyst support can have as ignificant impact on the rate of the pairwise addition of hydrogen. [12,13] Remarkably,t itania-supported metal catalysts were shown to exhibit much higher levels of the pairwise addition of hydrogen (and larger PHIP effects) relative to that exhibited by metals on other supports.…”
mentioning
confidence: 99%
“…[12,13] Remarkably,t itania-supported metal catalysts were shown to exhibit much higher levels of the pairwise addition of hydrogen (and larger PHIP effects) relative to that exhibited by metals on other supports. [9,14] Therefore, examination of the nature of the active sites for titania-supported nanoparticles in the contexto ft he pairwise addition of hydrogen may open up new possibilities for the rational preparation of catalysts that are able to maximize the observed PHIP effects and for the production of hyperpolarizedm olecular contrast agents potentially suitable for in vivo magnetic resonance imaging investigations. [14][15][16] In catalysis, it is well known that metals supported on titania exhibit the strong metal-support interaction (SMSI) effect.…”
mentioning
confidence: 99%